Analisis Statistik Presepsi Mahasiswa Teknik Kimia Angkatan 2023 Paralel C UPN “Veteran” Jawa Timur Sebagai Kampus Bela Negara Terhadap Efektifitas Rancangan Undang-Undang Perampasan Aset - Maulana Azis Alfahrezi; Muhamad Abiedama Fahrezi; Neo Harlan; Ahmad Rifaldi Prasetia (International Forum of Researchers and Lecturers, 2025)
The Draft Asset Forfeiture Law represents a significant step in combating economic crimes in Indonesia, focusing on non-conviction-based asset recovery. This study aims to analyze the perceptions of Chemical Engineering students (2023 Cohort, Parallel C) at UPN